1993
DOI: 10.3181/00379727-203-43623
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Zinc Influences DNA Strand Break and 8-Hydroxy-2'-Deoxyguanosine Levels in Infant Rhesus Monkey Liver

Abstract: Severe zinc deficiency in rodent models has been shown to influence the frequency of single-strand breaks in DNA isolated from liver. In the current study, we investigated whether DNA isolated from infant monkeys born to mothers fed zinc-restricted diets would be characterized by higher than normal levels of DNA damage. DNA was isolated from 30-day-old infants born to dams fed low zinc (2 or 4 micrograms Zn/g) or control zinc (50 micrograms Zn/g) diets. The amount of single-strand breaks in liver DNA was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…Increased oxidant production has been shown in cell cultures grown in zinc-deficient media [18]. In vivo, increases in oxidative protein and DNA damage has been shown in zinc-deficient rats [10,[19][20][21][22]. Zinc deficiency also increases the susceptibility to oxidative injury.…”
Section: Low Zinc and Increases In Oxidative Susceptibilitymentioning
confidence: 99%
“…Increased oxidant production has been shown in cell cultures grown in zinc-deficient media [18]. In vivo, increases in oxidative protein and DNA damage has been shown in zinc-deficient rats [10,[19][20][21][22]. Zinc deficiency also increases the susceptibility to oxidative injury.…”
Section: Low Zinc and Increases In Oxidative Susceptibilitymentioning
confidence: 99%
“…A significant proportion of North Americans do not ingest adequate zinc [3]. Based on the 2000-2001 NHANES data, approximately 12% of Americans do not consume the estimated average requirement for zinc and could be at risk for zinc deficiency [4].…”
Section: Introductionmentioning
confidence: 99%
“…Our data support the notion that functional consequences of zinc deficiency occur before plasma zinc concentrations decline and highlight the essential role of zinc for maintaining DNA integrity in vivo. Previous studies, using in vitro and in vivo animal models, found that zinc deficiency increased DNA damage in liver or testes (17,18,21,22). To our knowledge, our study is the first report of zinc-related DNA damage in peripheral blood cells of humans.…”
Section: Tablementioning
confidence: 99%
“…Overall, zinc deficiency may both increase oxidative stress and impair DNA integrity, thereby increasing the risk of cancer. In vitro and animal studies have clearly shown increased DNA damage and oxidative stress with zinc deficiency (14)(15)(16)(17)(20)(21)(22). However, the extent to which zinc depletion regulates ox-idative stress and DNA integrity in controlled human studies has yet to be comprehensively explored.…”
Section: Introductionmentioning
confidence: 99%